2016
DOI: 10.1039/c5sm02871j
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of contact angles and surface tensions of interfacial nanobubbles in ethanol aqueous solutions

Abstract: The astonishing long lifetime and large contact angles of interfacial nanobubbles are still in hot debate despite numerous experimental and theoretical studies. One hypothesis to reconcile the two abnormalities of interfacial nanobubbles is that they have low surface tensions. However, few studies have been reported to measure the surface tensions of nanobubbles due to the lack of effective measurements. Herein, we investigate the in situ contact angles and surface tensions of individual interfacial nanobubble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…178 Literature often suggests that they can only occur in supersaturated gas solutions 187 and that their cavitation is only related to pressure gradients and variations, contrary to temperature change, 192 yet this is opposed by experimental and theoretical reports. 189,193,194 While most research on this topic is performed with water, nanobubbles have also been reported for aqueous ethanol solutions 195 and protic nonaqueous solvents. 196 Bulk phase nanobubbles can be as small as 10 nm in diameter, 179 but typical sizes range between 100 and 300 nm.…”
Section: Bubble Mechanism: the Existential Crisis Of Nanobubblesmentioning
confidence: 99%
“…178 Literature often suggests that they can only occur in supersaturated gas solutions 187 and that their cavitation is only related to pressure gradients and variations, contrary to temperature change, 192 yet this is opposed by experimental and theoretical reports. 189,193,194 While most research on this topic is performed with water, nanobubbles have also been reported for aqueous ethanol solutions 195 and protic nonaqueous solvents. 196 Bulk phase nanobubbles can be as small as 10 nm in diameter, 179 but typical sizes range between 100 and 300 nm.…”
Section: Bubble Mechanism: the Existential Crisis Of Nanobubblesmentioning
confidence: 99%
“…In most experiments, the morphology of surface nanobubbles was imaged with AFM [1,2,[6][7][8][9][10][11][12][13][14][15] . The interaction between AFM tips and the surface nanobubbles certainly will influence the final images of such bubbles.…”
Section: Interaction Between Afm Tips and Pinned Surface Nanobubblesmentioning
confidence: 99%
“…Despite the relatively extensive AFM nanobubble measurements available, there still exist crucial discrepancies among different imaging modes (Carambassis et al, ; Ishida et al, ; Lou et al, ; Tyrrell and Attard, ; Yakubov et al, ). The most commonly used AFM techniques to study nanobubbles are amplitude‐modulation AFM (AM‐AFM) and PeakForce Quantitative Nano‐Mechanics (PF‐QNM) AFM (Lohse and Zhang, ; Yang et al, ; Zhao et al, ). AM‐AFM holds the advantage of being a dynamic‐resonant mode of imaging that leads to smaller tip‐sample forces than static‐ or quasi‐static‐mode methods (Garcia and Perez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nanobubbles have been previously studied by different methods such as electrochemical characterization (Yang et al ; Zhang et al, ), optical (Chan and Ohl, ; Chan et al, ; Karpitschka et al, ; Seo et al, ), and X‐ray (Zhang et al, ) imaging, and AFM (Yang et al, ; Zhao et al, ). The key parameters in their characterization are the contact angle and the surface tension (Attard and Miklavcic, ; Attard and Miklavcic, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation